Program Pembelajaran Bahasa Inggris: Menumbuhkan Minat Dan Kesediaan Anak-Anak Asli Papua Terhadap Belajar Tata Bahasa Dan Kosa Kata Bahasa Dalam Berbahasa Di Panti Asuhan Kartini Merauke - Marnina Marnina; Angla F Sauhenda (Lembaga Pengembangan Kinerja Dosen, 2024)
The implementataion of this service activity aims to determine the difficulties of Papua childrens in orphanages in mastering vocabulary and grammar in understanding English texts. Papuan children experience a lack of vocabulary mastery, lack of self confidence, fear of making mistakes, so it is hoped that with this training participants can improve their ability to use English vocabulary and grammar properly and correctly so that there will be an increase in participants’ skills in master English vocabulary. This service was carried out at the Kartini orphanage in Merauke in February 2024. The duration was 2 times a week namely Thursday and Friday for 3 months through the application of theory and practice with 20 native Papuan children. This service is carried out in the in the form of workshops, training, and mentoring, while the methods used are: (1) providing a handbook to be used during the activity which contains the materials that will be studied during the activity; (2) provide basic material; (3) provide training on vocabulary and grammar to measure the participants’ mastery of vocabulary and grammar. The expected results of this service are: (1) growing interest in indigenous Papuan children learning grammar and vocabulary in the language; (2) increasing knowledge of English vocabulary aand grammar of native Papuan children; (3) increasing English readings skills.